Clinicopathological features, therapeutic options, and significance of CD103 expression in 15 patients with follicular mucinosis - Wang, Jiaqi; Wang, Yanqing; Zhou, Hongyu; Wang, Ping; Zhu, Mengyan; Li, Liuyu; Shen, Hong (Frontiers in Medicine, 2023)
Background: Follicular mucinosis (FM) is generally divided into a primary benign idiopathic form and a secondary form associated with mycosis fungoides. Objective：To analyze the clinical and pathological features of FM and explore the pathological significance of CD103 expression. Methods: In this case series, we retrospective analysis the clinical, pathological, treatment and follow-up treatment of 15 cases of FM. The expression of CD103 in all cases was detected by immunohistochemistry. Result: A total of 15 patients were enrolled, 7 were primary follicular mucinosis (P-FM) and 8 were mycosis fungoides-associated follicular mucinosis (MF-FM). Lesions of both P-FM and MF-FM are difficult to distinguish, present with red or dark red plaques and follicular papules. Pathologically, MF-FM showed more significant infiltrates of folliculotropic lymphoid cells, and the amount and proportion of CD103+ cells were significantly higher than that in P-FM. Follow-up data were available for 13 patients. 3 cases were resolved after surgical resection, 2 patient was marked improved after oral administration of hydroxychloroquine and three times ALA photodynamic therapy respectively. The rest patients showed only modest efficacy. Conclusion: FM should be differentiated based on pathological characteristics and treatment response, CD103 is helpful in differential diagnosis of FM.